Face Pareidolia Recruits Mechanisms for Detecting Human Social Attention. (August 2020) - Palmer, Colin J.; Clifford, Colin W. G.
Face pareidolia is the phenomenon of seeing facelike structures in everyday objects. Here, we tested the hypothesis that face pareidolia, rather than being limited to a cognitive or mnemonic association, reflects the activation of visual mechanisms that typically process human faces. We focused on sensory cues to social attention, which engage cell populations in temporal cortex that are susceptible to habituation effects. Repeated exposure to "pareidolia faces" that appear to have a specific direction of attention causes a systematic bias in the perception of where human faces are looking, indicating that overlapping sensory mechanisms are recruited when we view human faces and when we experience face pareidolia. These cross-adaptation effects are significantly reduced when pareidolia is abolished by removing facelike features from the objects. These results indicate that face pareidolia is essentially a perceptual phenomenon, occurring when sensory input is processed by visual mechanisms that have evolved to extract specific social content from human faces.